Risk factors for Turkish Cypriot patients with coronary artery disease - Conkbayır, Cenk; Öztaş, Didem Melis; Uğurlucan, Murat (Termedia Publishing House, 2020)
Introduction: Ischemic heart disease is the leading cause of death worldwide. In this study, we evaluated the risk factors for Turkish Cypriot ischemic heart disease patients. Material and methods: In this study we examined 7017 patients, retrospectively. 5.9% of the patients had myocardial infarction coronary artery disease (MICAD) and 94.1% of the patients were control patients. The mean age of the study population was 52, and 39.2% were female. The risk factors considered were: age, sex, hypertension (HT), diabetes mellitus (DM), family history of coronary artery disease, smoking, high total cholesterol levels and obesity. Results: Consistently with the presumed risk factors, there was a significant difference between MICAD and control groups in our study for smoking, HT, DM and obesity. However, our study revealed no significant difference for high total cholesterol levels in contrast to the current literature. Assessing the risk factors among male and female patient groups separately, both men and women have the highest risk prevalence for hypertension. Smoking is the second most common risk factor among males, whereas it is the family history of coronary heart disease in the female group. HT, DM and obesity were found to be significant risk factors for both males and females in our study group, while family history was revealed to be significant only in women. Conclusions: Modifiable risk factors such as smoking, hypertension, diabetes mellitus and obesity may be controlled by lifestyle changes and medical therapies, and should be approached with caution for preventing cardiac events. Non-modifiable risk factors such as age, gender, family history and ethnicity should be taken into account for disease prediction.
Keywords: Coronary Artery Disease; Myocardial Infarction; Risk Factors